Lysophosphatidylcholine increases the neurotoxicity of Alzheimer's amyloid β1-42 peptide: Role of oligomer formation. (30th April 2015) - Sheikh, A. Md.; Michikawa, M.; Kim, S.U.; Nagai, A.
Highlights: LPC increases Aβ-induced apoptotic cell death in a neuronal culture. LPC increases Aβ-induced Bax and active caspase9 level in a neuronal culture. LPC augments Aβ oligomer formation in cell culture condition. Removal of early-formed Aβ oligomer decreases toxicity enhancing effects of LPC. LPC increases Aβ-induced ROS level in a neuronal culture. Abstract: Oligomer formation is considered as a critical process for the neurotoxic effects of Alzheimer's amyloid β (Aβ) peptide. Previously we have demonstrated that lysophosphatidylcholine (LPC) increases the oligomer formation of Aβ1–42, the major Aβ peptide found Alzheimer's disease (AD) lesions. In this study, we have investigated whether LPC affects the neurotoxic effects of Aβ1–42 in a neuronal cell line (A1) culture. Dimethyl thiazolyl diphenyl tetrazolium (MTT) assay revealed that up to 10 μM concentration, LPC did not affect A1 cell viability. Aβ1–42 decreased the cell viability, and such effect was dose dependently enhanced by LPC. However, neither LPC nor Aβ1–42, alone or in combination increased lactate dehydrogenase (LDH) release from A1 cells after 24-h treatment. Terminal deoxynucleotidyl transferase dUTP-biotin nick-end-labeling (TUNEL) assay showed that LPC increased Aβ1–42 -induced apoptotic cell number. To determine the underlying mechanisms, the proteins implicated in apoptosis pathways including Bcl-2- and caspase-family were analyzed by Western blotting. The results demonstrated that Aβ1–42 decreased Bcl-2 in A1 cells at 24 h, whereas LPC had no effect at any time point. Both LPC and Aβ1–42 increased Bax level at 24 h, and their combined stimulation showed a synergistic effect. Similar synergistic effect of LPC and Aβ1–42 on caspase9 activation was observed. Dot blot immunoassay and Western blotting showed that LPC augmented Aβ1–42 oligomer formation in cell culture medium. Removing LPC-induced early-formed Aβ1–42 oligomer from the culture medium by immunoprecipitation decreased active caspase9 level and neurotoxicity, as revealed by Western blotting and MTT assay. Furthermore, dihydroethidium (DHE) assay showed that Aβ1–42 increased reactive oxygen species level in A1 cells, such effect was further enhanced by LPC. Thus, our results demonstrated that LPC increased the oligomer formation process of Aβ1–42 peptide in culture condition, and consequently increased apoptotic neuronal death. Such process might be important for the pathogenesis of AD, and inhibition of LPC generation could be a therapeutic target for the disease.